The Ideal Teacher Profile in the Perspective of Class VI Students in Madrasah Ibtidaiyah 12 Padang Sappa, Ponrang District, Luwu Regency - Umrah Umrah (Jurnal Konsepsi, 2019)
This research is a qualitative descriptive field research that analyzes the data in depth based on the percentage of numbers. The results showed that: 1. The ideal teacher profile in the perspective of class VI Madrasah Ibtidaiyah 12 Padang Sappa, Ponrang District, Luwu Regency includes: a. Have an exemplary attitude in behavior, fear God Almighty, develop praiseworthy attitudes in everyday life, b. Interact and communicate well with school residents, c. Carry out guidance and counseling for students, d. Prepare learning administration, e. Mastering learning material, f. Maintain a harmonious relationship, h. Assess and praise the results in the teaching and learning process carried out by students. From the research and questionnaire results, it was found that: a. Teachers have exemplary attitudes in behavior, preach to God, and behave praiseworthy at MI 12 Padang Sappa received the most "own" answers as much as 50% .. b. Teachers have the ability to develop professionally, interact with fellow teachers, students and even others, respondents choose the answer "very have" with a score of 50% 66%., D. The teacher has the ability to prepare the learning administration. Got the answer "really has" as much as 76%, e. Teachers mastering the learning material get the answer "master" as much as 50%, f. The teacher maintains a harmonious relationship with a score of 50% from the answer "very caring", g. The teacher assesses and praises the results in the teaching and learning process carried out by students and gets the answer "sometimes" gets 50% answer. 2. Increasing student learning achievement is very much determined by the ideal teacher profile where the smarter and more skilled a teacher is in educating students, the students will produce good achievement.